ALGORITHM OF FORMATION OF MARKETING STRATEGY OF THE TOURIST ENTERPRISE - Nelina, V.; Shevchenko, B. (My University, 2021)
In the tourism industry, we can state a certain freedom of strategic choice: to pursue limited or broad marketing goals, to use the competitive advantages of low costs or their differentiation. Some of the approaches can be used simultaneously. It should be noted, however, that the set of strategic capabilities of the tourism organization is limited by the capabilities of the industry and the conditions of competition in it, the competitiveness of the organization, its market position and capabilities. The main tasks in determining the starting point for the formation of strategies are the choice of key areas and their relationship with other aspects of organizational management (marketing, finance, current management, etc.).
Keywords: ALGORITHM OF FORMATION OF MARKETING STRATEGY OF THE TOURIST ENTERPRISE